Producción de taxol y taxanos relacionados en cultivos de células en suspensión de Taxus globosa (Schltdl) - Tapia Barrera, Nadia Primavera (Universidad Autónoma Metropolitana, 2014)
Taxus globosa Schltdl. (Taxaceae) "Mexican yew", is the only species of the genus Taxus growing in Mexico. Due to the rarity of the species, slow growth and low population density, the tree is protected by the Secretary of Environment and Natural Resources (SEMARNAT). The wild tree T. globosa has been studied from the phytochemical point of view from 2000 up to this date, showing that the species produces taxol and taxanes, related to important anticancer activity; unlike other species of Taxus, the largest accumulation of taxol occurs in the leaves and young stems. Objective. Because of the importance of its biosynthetic potential in connection with the production of bioactive taxanes, in vitro cultures of T. globosa were initiated to evaluate the different biotechnological strategies such as: type of culture, the culture medium formulation, batch type culture and cultivation in two phases, the use of stimulators and cell immobilization, in order to increase the production of taxol and related taxanes, and stimulate its excretion into the culture medium. Results. Experiments for the establishment of callus cultures and suspension cells were carried out, and as a result, obtained calli derived from young leaves and stems of T. globosa time from 20 days to Gamborg (B5) addition of 2,4-dichlorophenoxyacetic acid (2,4- D) (2 mg/L), kinetin (KN) (0.5 mg/L) and gibberellic acid (GA3) (0.25 mg/L). Growth and taxane production in callus cultures were evaluated in two culture media: Woody Plant Medium (WPM) and B5 added picloram (PIC) (2 mg/L), KN (0.1 mg/L) and GA3 (0.5 mg/L). Callus grown on B5 medium showed a growth index (GI) of 0.44, and a doubling time (dt) of 13.81 days. Furthermore, callus cultured in medium WPM had higher GI (0.70), and a td of 13.2 days. The callus cultures grown in the two mediums (B5 and WPM), produced taxol and 3 taxanes including: baccatin III, 10-deacetylbaccatin III, and 10-deacetiltaxol. These taxanes are produced from the start to the end of the cultures, cyclically, reaching the highest production of taxol in the B5 medium, during the 1st week (50 µg/g PS) of culture; this doubled up production, and obtained it in less time than medium WPM (24 µg/g PS). The cell suspension cultures were established from friable calli derived from T. globosa leaves. Experiments were carried out to determine the size of the inoculum most suitable for this species (50, 100 and 150 g FW/L); it was determined that the inoculum size of 50 g FW/L was the best suited to establish the kinetics of cellular growth in medium WPM, in the batch type culture cell suspension of T. globosa; an IG of 0.65 and 3.9 days dt were obtained. In establishing the batch type culture cell suspensions, the WPM and B5 media added PIC (2 mg/L), KN (0.1 mg/L) and GA3 (0.5 mg/L), and the stimulation of methyl jasmonate (MeJ) (100 µM), were evaluated. The medium that stimulated cell growth was the WPM with a GI of 6.14 and a td of 2.32 days. The WPM culture medium with MeJ added, stimulated production of taxol (197.999 µg/L) and three taxanes more, such as 10- deacetylbaccatin III (633.724 µ/L), 10-deacetiltaxol (229.611 µg/L) and baccatin III (160.622 µg/L). Based on the assessment of the results obtained for the WPM and B5 media, where we observe that the WPM stimulated cell growth and the B5 medium stimulated excretion of taxanes in the culture medium, it was decided to test for the first time in liquid cultures of T. globosa, the strategy type culture batch in two phases and stimulation with calcium (Ca2+) and MeJ. At this stage it was confirmed that the MeJ inhibits cellular growth in cultures of T. globosa. Regarding the production of taxanes, observing the effect of Ca2+ combined with MeJ, the productivity of 3 taxanes increased: taxol (16.299 - 34.516 µg/L day-1 ), baccatin III (4.673 - 26.287 µg/L day-1 ) and cephalomannin (2.435 - 151995 µg/L day-1 ) with an excretion of 41 to 60%; this biotechnology strategy was unsuccessful, it did not to stimulate production of 10-deacetiltaxol. In the last stage of the research, it was evaluated for the first time, in cell cultures of the Mexican yew, the effect of cellular immobilization and stimulation with MeJ (100 µM), in medium Gamborg B5 (B5) added of two treatments containing 2,4-D (T1) and PIC (T2), in combination with KN and benzylaminopurine (BAP). To this end, batch-type cultures in two stages were used, with the goal to stimulate in the second phase or production, the biosynthesis of taxane over the time factor, and also its excretion in the cell cultures of T. globosa. Productivity and the rate of excretion into the culture medium of 4 taxanes: baccatin III (8.260 - 12.7888 µg/L day-1 ) (81%); 10-deacetylbaccatin III (15 µg/L day-1 ); 10 deacetiltaxol (3.180 µg/L day-1 ) (62%) and cephalomannin (49.272 µg/L day-1 ), was mainly stimulated by the effect of treatment T1 in the crop of free cells, and stimulated it with MeJ, from the third day and until the end of the second kinetics phase. Conversely, the productivity of taxol (53 µg/L day-1 ) was obtained by treatment effect of T2 MeJ added intracellularly in both free and immobilized cells; the time of the taxol biosynthesis in vitro decreased frolm 15 days to 3 days in the production phase, doubling up its productivity (130.347 µg/L day-1 ) in cultured and immobilized cells, stimulated with MeJ of T. globosa. Our results indicate that to stimulate the production of precursors of taxol (baccatin III and 10-deacetylbaccatin III), in addition to the cephalomannin and the 10-deacetiltaxol, it is not necessary to immobilize the cells in suspension cultures of the species. Furthermore, the rate of taxol biosynthesis in vitro was increased by the effect of cell immobilization and encouragement of methyl jasmonate in synergy with the carbon sources used in this research.; Taxus globosa Schltdl. (Taxaceae) “tejo mexicano”, es la única especie del género Taxus que crece en la República Mexicana. Por la rareza de la especie, por su lento crecimiento y poca densidad poblacional, es un árbol protegido por la Secretaria del Medio Ambiente y Recursos Naturales (SEMARNAT). El árbol silvestre de T. globosa ha sido estudiado desde el punto de vista fitoquímico desde 2000 a la fecha, demostrando que la especie produce taxol y taxanos relacionados con importante actividad anticancerígena, a diferencia de otras especies de Taxus, la mayor acumulación de taxol ocurre en las hojas y en los tallos jóvenes. Objetivo. Dada la importancia de su potencial biosintético con respecto a la producción de taxanos bioactivos, se iniciaron los cultivos in vitro de T. globosa, para evaluar diferentes estrategias biotecnológicas como son: el tipo de cultivo, formulación del medio de cultivo, cultivo tipo lote y cultivo en dos fases, el uso de estimuladores e inmovilización celular, con la finalidad de incrementar la producción de taxol y taxanos relacionados y estimular su excreción al medio de cultivo. Resultados. Se realizaron los experimentos de establecimiento de los cultivos de callo y células en suspensión, donde se obtuvieron callos derivados de hojas y tallos jóvenes de T. globosa a partir del tiempo 20 días en medio Gamborg (B5) añadido de ácido 2,4- diclorofenoxiacético (2,4-D) (2 mg/L), cinetina (CN) (0.5 mg/L) y ácido giberélico (GA₃) (0.25 mg/L). El crecimiento y la producción de taxanos en cultivos de callo se evaluó en dos medios de cultivo: Woody Planta Medium (WPM) y B5 añadidos de picloram (PIC) (2 mg/L), CN (0.1 mg/L) y GA₃ (0.5 mg/L). Los callos cultivados en medio B5 presentaron un índice de crecimiento (IC) de 0.44 y un tiempo de duplicación (td) de 13.81 días. Por otro lado, los callos cultivados en medio WPM tuvieron mayor IC (0.70) y un td de 13.2 días. Los cultivos de callos cultivados en los dos medios (B5 y WPM) produjeron taxol y 3 taxanos entre ellos: la baccatina III, 10-deacetilbaccatina III y 10-deacetiltaxol; estos taxanos se producen desde el inicio de los cultivos y hasta el final de los mismos en forma cíclica, obteniendo la mayor producción de taxol en el medio B5 durante la 1ª semana (50 µg/g PS) de cultivo, esta producción fue el doble y se obtuvo en menor tiempo que en el medio WPM (24 µg/g PS). Los cultivos de células en suspensión se establecieron a partir de callos friables derivados de hojas de T. globosa. Se realizaron los experimentos para determinar el tamaño de inóculo más adecuado para esta especie (50, 100 y 150 g PF/L), donde se determinó que el tamaño de inóculo de 50 g PF/L fue el adecuado para establecer las cinéticas de crecimiento celular en medio WPM, en los cultivos tipo lote de células en suspensión de T. globosa y se obtuvo un IC de 0.65 y un td 3.9 días. En el establecimiento de los cultivos tipo lote de celulas en suspensión se evaluaron los medios WPM y B5 añadidos de PIC (2 mg/L), CN (0.1 mg/L) y GA₃ (0.5 mg/L) y la estimulación con jasmonato de metilo (MeJ) (100µM). El medio que estimuló el crecimiento celular fue el WPM con un IC de 6.14 y un td de 2.32 días. El medio de cultivo WPM añadido de MeJ estimuló la producción del taxol (197.999 g/L) y tres taxanos más como son 10-deacetilbaccatina III (633.724 g/L), 10-deacetiltaxol (229.611 g/L) y baccatina III (160.622 g/L). En base a los resultados obtenidos en la evaluación de los medios WPM y B5, donde observamos que el WPM estimuló el crecimiento celular y por otro lado, el medio B5 estimuló la excreción de los taxanos al medio de cultivo, se decidió evaluar por primera vez en cultivos líquidos de T. globosa, la estrategia de cultivos tipo lote en dos fases y la estimulación con calcio (Ca²⁺) y MeJ. En esta etapa se corroboró que el MeJ inhibe el crecimiento celular en los cultivos de T. globosa. Con respecto a la producción de los taxanos, observandose que el efecto del Ca2+ combinado con el MeJ incrementó la productividad de 3 taxanos: taxol (16.299 – 34.516 µg/L día⁻¹ ), baccatina III (4.673 – 26.287 µg/L día⁻¹ ) y cefalomanina (2.435 – 151.995 µg/L día⁻¹ ) con una excreción de 41 al 60 %, con esta estrategia biotecnológica no se logró estimular la producción del 10-deacetiltaxol. En la última etapa del trabajo de investigación, se evaluó por primera vez en los cultivos celulares del tejo mexicano, el efecto de la inmovilización celular y la estimulación con MeJ (100 µM), en medio Gamborg B5 (B5) añadido de dos tratamientos que contenían 2,4-D (T1) y PIC (T2), en combinación con CN y benzilaminopurina (BAP). Para ello se empleó los cultivos tipo lote en dos fases, con la finalidad de estimular en la segunda fase o de producción, la biosíntesis de los taxanos con respecto al factor tiempo, así como su excreción en los cultivos celulares de T. globosa. La productividad y el porcentaje de excreción al medio de cultivo de 4 taxanos: baccatina III (8.260 – 12.7888 µg/L día⁻¹ )( 81%); 10-deacetilbaccatina III (15 µg/L día⁻¹); 10 deacetiltaxol (3.180 µg/L día-1 )( 62%) y cefalomanina (49.272 µg/L día⁻¹ ), se estimuló principalmente, por efecto del tratamiento T1 en los cultivos de células libres y estimulados con MeJ, a partir del tercer día y hasta al final de la segunda fase de la cinética. Por el contrario, la productividad del taxol (53 µg/L día-1 ) se obtuvo por efecto del tratamiento T2 añadido de MeJ de manera intracelular tanto en células libres como inmovilizadas, el tiempo de la biosíntesis in vitro del taxol disminuyó de 15 días a 3 días en fase de producción, incrementando al doble su productividad (130.347 µg/L día-1 ) en los cultivos de células inmovilizadas y estimuladas con MeJ de T. globosa. Nuestros resultados indican que para estimular la producción de los precursores del taxol (baccatina III y 10-deacetilbaccatina III) además de la cefalomanina y el 10-deacetiltaxol, no es necesario inmovilizar los cultivos de células en suspensión de la especie. Asimismo, la velocidad de biosíntesis del taxol in vitro se incrementó por efecto de la inmovilización celular y del estímulo del jasmonato de metilo en sinergia con las fuentes de carbono utilizadas en esta investigación.